2017
DOI: 10.5194/gmd-10-2905-2017
|View full text |Cite
|
Sign up to set email alerts
|

REDCAPP (v1.0): parameterizing valley inversions in air temperature data downscaled from reanalyses

Abstract: Abstract. In mountain areas, the use of coarse-grid reanalysis data for driving fine-scale models requires downscaling of near-surface (e.g., 2 m high) air temperature. Existing approaches describe lapse rates well but differ in how they include surface effects, i.e., the difference between the simulated 2 m and upper-air temperatures. We show that different treatment of surface effects result in some methods making better predictions in valleys while others are better in summit areas. We propose the downscali… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 48 publications
(65 reference statements)
0
47
0
Order By: Relevance
“…To assess the performance of the PZI model, we conducted a 10‐fold cross‐validation. This is a commonly used method to compare and select a model for a given predictive modeling problem and it generally has a lower bias than other methods such as a simple split of training and test data (e.g …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To assess the performance of the PZI model, we conducted a 10‐fold cross‐validation. This is a commonly used method to compare and select a model for a given predictive modeling problem and it generally has a lower bias than other methods such as a simple split of training and test data (e.g …”
Section: Methodsmentioning
confidence: 99%
“…It is well known that the total permafrost simulation chain may be significantly affected by the choice of input data sets . ERA‐Interim, produced by the European Center for Medium‐range Weather Forecast (ECMWF), was chosen for this study as it was found to describe the complex environments over the QTP better than other re‐analyses, and its downscaled results have achieved promising results (e.g …”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…ERA‐Interim reanalysis data, produced by the European Center for Medium‐Range Weather Forecasts, have been well proven to resolve near‐surface air temperature for various mountain regions (Bao & Zhang, ; Fiddes et al, ). Cao, Gruber, and Zhang () proposed an advanced downscaling approach by incorporating the parameters related to cold air pooling (or winter inverse). The downscaled 2‐m air temperature had been validated against the in situ measurements with a high‐degree match over the Qilian Mountains during 2012–2016 (Cao, Gruber, & Zhang, ).…”
Section: Study Site and Methodsmentioning
confidence: 99%
“…Cao, Gruber, and Zhang () proposed an advanced downscaling approach by incorporating the parameters related to cold air pooling (or winter inverse). The downscaled 2‐m air temperature had been validated against the in situ measurements with a high‐degree match over the Qilian Mountains during 2012–2016 (Cao, Gruber, & Zhang, ). Figure shows the downscaled 2‐m air temperature in our study area during 2006–2011.…”
Section: Study Site and Methodsmentioning
confidence: 99%